Flattery Harm in Social Interactions and its Pathology from Imam Ali's Viewpoint - Omid Ebrahimi; Mansour Bayrami; Delaram Mohammadi (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: The issue of flattery and its individual and social consequences are regarded as a moral vice in many human societies and the higher degree of this trait in the society, the more regression and decline. Therefore, the aim of this study was to examine the harms of flattery in the social relations and its pathology from Imam Ali's viewpoint. Method: This study was conducted through reviewing texts, and the authors have tried to study different dimensions and damages of the flattery in social interactions, using books and articles in the associated fields of religious sciences and psychology with an emphasis on the Nahjol-Balagheh. The researchers declared no conflicts of interest. Results: The results showed, in the view of Imam Ali, flattery stems from stupidity and humiliation, those in power who like flattering, and the culture of fostering flattering. This is all rooted in atheism and ignorance, the ultimate goal being ego and its outcome being humiliation. Conclusion: Based on the results, it can be concluded that flattering in humans is a relational matter and it results from the action and interaction of the strong and the weak, a social harm which dates back to long time ago, threatening social health. For downloading the full-text of this article please click here. Please cite this article as: Ebrahimi O, Bayrami M, Mohammadi D. Flattery Harm in Social Interactions and its Pathology from Imam Ali's Viewpoint. J Res Relig Health. 2019; 5(3): 137- 149. doi: https://doi.org/10.22037/jrrh.v5i3.18632